PENERAPAN STRATEGI PEMBELAJARAN LANGSUNG DENGAN METODE DRILL UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN KETERAMPILAN PELAKSANAAN IBADAH POKOK BAHASAN PENGURUSAN JANAZAH DI MTs AL-MA’SHUM RANTAUPRAPAT LABUHANBATU - Muhammad Abri Harahap (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: This Class Action Research is executed to utilize to improve study of maintenance of corpse lesson at IX grade (female) at MTs Al-Ma’shum Rantauprapat Labuhanbatu. This research is aimed to: (1) knowing learning outcomes on the subject maintenance of corpse before using method Drill. (2) knowing implementation learning on the subject maintenance of corpse after using method Drill. (3) knowing student learning outcomes on the subject maintenance of corpse after using method Drill. (4) Knowing improved skills students on the subject maintenance of corpse with using method Drill. (5) knowing evaluate the response of the students learning during the learning process with using method Drill on the subject maintenance of corpse. This research is executed on 09th of February till 15nd of May 2015. The Location of this research is at Mts Al-Ma’shum Rantauprapat Labuhanbatu city North Sumatera. The subyek of this research are the female students of IX year consist of 29 students. Action done in 3 (three) cycles. Each cycle consist of planning step, execuation of action and observation of reflection. Studying was designed with strategy study of direct instruction with method Drill. Data collecting pass by direct observation to educative participant activity parameter in study group with teachear guidance. Technique of written and practical test done to get data is make-up of result leran educative participant at cognate domain and psychomotoric. Enquette and interview used to collect data of educative participant response to strategy study of direct instruction which is applied.